Discourse on the Coretax System in Indonesia: A Study of Legal Certainty and Guarantees for Taxpayers - Arifin, Dharmawan; Santoso, Aris Prio Agus; Poniman, Poniman (The Easta Journal Law and Human Rights, 2025)
Digitalization of Taxation in Indonesia refers to the process of utilizing digital technology and electronic systems to manage, process, and report tax obligations. The Directorate General of Taxes (DGT) employs various applications such as e-Filing, e-Billing, e-Invoice, and other supporting applications. However, one of the main issues is the lack of integration between these applications, leading to unachieved taxpayer compliance, insufficient legal certainty, and weak legal protection guarantees. Enhancing integrated tax digitalization through the Coretax application offers an easy and efficient solution for taxpayers. This study aims to analyze the implementation of the Core Tax Administration System (CTAS) within the Coretax application to improve the number of compliant taxpayers in Indonesia, ensure legal certainty, and provide guarantees for the protection of taxpayers' personal data. The research employs a qualitative method through normative studies and journals related to CTAS. The results of the study are as follows: the ease of use of the Coretax application and its adherence to existing legal frameworks in business processes effectively increase the number of compliant taxpayers. Additionally, incorporating integrated and comprehensive legal foundations for CTAS, such as Presidential Regulation No. 40 of 2018 and Minister of Finance Regulation No. 81 of 2024, enhances legal certainty. Furthermore, the guarantee of data protection through the Personal Data Protection Law (PDP Law) and relevant international regulations ensures the confidentiality of participants' data.